2023
DOI: 10.3390/s23094209
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Fringe-to-Phase Framework for Single-Shot 3D Reconstruction Integrating Structured Light with Deep Learning

Abstract: Three-dimensional (3D) shape acquisition of objects from a single-shot image has been highly demanded by numerous applications in many fields, such as medical imaging, robotic navigation, virtual reality, and product in-line inspection. This paper presents a robust 3D shape reconstruction approach integrating a structured-light technique with a deep learning-based artificial neural network. The proposed approach employs a single-input dual-output network capable of transforming a single structured-light image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…It should be noted that alternative output vectors, such as multiple phase-shifted fringe images or wrapped phases with different frequencies, can be used instead of numerators and denominators. However, recent studies [ 39 , 70 , 71 , 75 ] have demonstrated that the spatial F2ND approach yields similar results to the fringe-to-fringe approach while requiring less storage space due to fewer channels in the output vector. Moreover, the fringe-to-wrapped phase approach is not considered ideal as it produces inferior results compared with the spatial F2ND approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that alternative output vectors, such as multiple phase-shifted fringe images or wrapped phases with different frequencies, can be used instead of numerators and denominators. However, recent studies [ 39 , 70 , 71 , 75 ] have demonstrated that the spatial F2ND approach yields similar results to the fringe-to-fringe approach while requiring less storage space due to fewer channels in the output vector. Moreover, the fringe-to-wrapped phase approach is not considered ideal as it produces inferior results compared with the spatial F2ND approach.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the DFFS dataset, the first temporal output slice includes both numerators and denominators (i.e., [s,0,h,w,0] and [s,0,h,w,1]). In contrast, the second temporal output slice only consists of a single fringe order map [ 75 ] or a single coarse map [ 39 ] (i.e., [s,0,h,w,0]), resulting in a missing channel in the second temporal output slice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wrapped phases of different frequency patterns are extracted by deep learning from a single composite fringe pattern to obtain the absolute phase. Nguyen et al [44] proposed a single-input dual-output network that obtains phase-shifted fringe images and coarse absolute phase maps from a single fringe pattern to achieve more accurate phase unwrapping. Compared to traditional methods, although the above methods based on deep learning accomplish 3D measurement with fewer patterns, they still use 8-bit sinusoidal patterns and lose the advantage of 1-bit patterns.…”
Section: Introductionmentioning
confidence: 99%